(3eajO GdYHGO ShGA GdYGca ajg hGdHGOs - (3CMeO Hf GdHTjQ GdYdGhis; (3GHf YGTQ , GHf YGTQ,J (B1040 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf WdH (B( (3GdYde (B) (3ef GaVd GdWGYGJ hGdbQHGJ CQOJ Cf CUfY YdjgG JbjjOkG hSejJg hSHH JSejJg Cf HYV GdENhGf ai GdefGe , hCQTOg Edi JSejJg agPG GdGSe , hEjGc CjgG GdfGXQ Cf jNOYc GdTjWGf s
(3BNQgG (B:s
(3hGHf CHj LeQI ai CKfGA cdGe dg eGfUg (B: (3hef cGf VYjakG dGjbOQ Ydi gPg GdgLQI adGjged faSg HGdcdjI , aEf Pdc YdGeI GdNSQGf , hdjCNP faSg HGdQab hGdMGjSI ai GdLgGO hGdgLQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeI ef ecJHI GdeUWai Hf HGHGfG s
(3ChQGbgG eJBcdI heJbUaI s
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3HBNQgG NGJeI JTJed Ydi KdGK hSJjf aGFOI s
Keywords: (3Gdabg GdESdGejs